Rare earth zirconate high-entropy ceramic fiber aerogel, preparation method and application thereof
Patent Information
- Application Number
- CN202611395019.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
目前,常用的纤维气凝胶大多选用具有高热稳定性的硅酸铝纤维、石英纤维或莫来石纤维作为纤维基体,普遍存在使用温度不够高,高温下热导率上升过快等问题
[0015] This invention provides a method for preparing rare-earth zirconate high-entropy ceramic fiber aerogel, comprising the following steps: mixing a flexible rare-earth zirconate ceramic fiber membrane with deionized water containing polyacrylamide to obtain a ceramic fiber dispersion; the chemical composition of the flexible rare-earth zirconate ceramic fiber membrane is A. 2-x B 2+x O7; the A 2-x B 2+x In O7, A represents trivalent rare earth ions, B represents tetravalent zirconium ions, and A can be La, Nd, Sm, Gd, or Yb, with x ranging from 0 to 0.3. The nano-silica dispersion and the ceramic fiber dispersion are mixed to obtain a mixture. A portion of the mixture or a portion of the ceramic fiber dispersion is sequentially subjected to rotary freezing and ice crushing to obtain ice crystals. The ice crystals are added to the remaining mixture or the remaining ceramic fiber dispersion for liquid nitrogen freezing to obtain a frozen block. The frozen block is freeze-dried to obtain a fiber aerogel preform. The fiber aerogel preform is sintered to obtain the rare earth zirconate high-entropy ceramic fiber aerogel. The preparation method of this invention employs both ice-templating and freeze-drying methods. The ice-templating method adds ice crystals before liquid nitrogen freezing, preventing ice crystal growth from the bottom during freezing and ensuring fiber orientation, thus avoiding anisotropy in the preform. Freeze-drying removes the solvent through ice crystal sublimation, eliminating liquid phase surface tension throughout the process and preventing pore collapse and preform shrinkage. Therefore, the rare earth zirconate high-entropy ceramic fiber aerogel prepared by the preparation method of the present invention is composed of ceramic fibers overlapping each other, and has low density, high porosity, low thermal conductivity and certain compression resilience.
Smart Images

Figure CN122916658A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-temperature resistant thermal insulation ceramics technology, and in particular to a rare earth zirconate high-entropy ceramic fiber aerogel, its preparation method, and its application. Background Technology
[0002] Rare earth zirconate ceramics A₂B₂O₇ (where A represents lanthanide rare earth elements and B represents Zr) are oxide ceramics composed of lanthanide rare earth elements and Zr. A₂B₂O₇ can be divided into two crystalline phases, pyrochlore and fluorite, both belonging to the cubic phase structure, depending on the size of the rare earth ion radii. Generally, for a single rare earth zirconate crystal structure, when r(A) 3+ ) / r(Zr 4+ The value of r(A) is 1.46~1.78, mainly exhibiting a pyrochlore texture. 3+ ) / r(Zr 4+ When the phosphonon conductivity (Pt) is less than 1.46, the fluorite structure is relatively stable. Regardless of whether it's a pyrochlore or fluorite structure, each basic unit of the rare-earth zirconate crystal contains an oxygen vacancy, which increases phonon scattering in the crystal structure, resulting in a lower intrinsic thermal conductivity for A₂B₂O₇. Furthermore, A₂B₂O₇ ceramic materials lack a phase transition point, possess high melting point (>2300℃), high chemical stability (maintaining structural stability above 2000℃), low lattice thermal conductivity, and good mechanical properties, making them ideal high-temperature resistant ceramic fiber matrix materials with significant application potential in high-temperature insulation candidate materials.
[0003] In recent years, fibrous aerogels, porous solid materials with a three-dimensional network structure formed by interlocking fibers, have attracted much attention. These fibrous aerogels typically possess a micron-scale pore structure and exhibit extremely low density, extremely low thermal conductivity, and extremely high porosity, as well as excellent resilience, adsorption, and thermal insulation properties. Currently, most commonly used fibrous aerogels utilize aluminosilicate fibers, quartz fibers, or mullite fibers with high thermal stability as the fiber matrix. However, these materials generally suffer from problems such as insufficient operating temperature and excessively rapid increase in thermal conductivity at high temperatures. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a rare earth zirconate high-entropy ceramic fiber aerogel, its preparation method, and its application. The rare earth zirconate high-entropy ceramic fiber aerogel prepared by the method has high porosity, low thermal conductivity, low density, and certain compression resilience.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing rare earth zirconate high-entropy ceramic fiber aerogel, comprising the following steps: A flexible rare-earth zirconate ceramic fiber membrane was mixed with deionized water containing polyacrylamide to obtain a ceramic fiber dispersion; the chemical composition of the flexible rare-earth zirconate ceramic fiber membrane is A. 2-x B 2+x O7; the A 2-x B 2+x In O7, A is a trivalent rare earth ion, B is a tetravalent zirconium ion, and A can be La, Nd, Sm, Gd, or Yb. The value of x ranges from 0 to 0.3. The nano-silica dispersion and the ceramic fiber dispersion are mixed to obtain a mixture; A portion of the mixture or a portion of the ceramic fiber dispersion is sequentially subjected to rotary freezing and ice crushing to obtain ice crystals; The ice crystals are added to the remaining mixture or the remaining ceramic fiber dispersion and frozen with liquid nitrogen to obtain frozen blocks; The frozen block was freeze-dried to obtain a fiber aerogel preform; The fiber aerogel preform is sintered to obtain the rare earth zirconate high-entropy ceramic fiber aerogel.
[0006] Preferably, the mass percentage concentration of polyacrylamide in the deionized water containing polyacrylamide is 0.1%. The mass ratio of flexible rare earth zirconate ceramic fiber membrane to polyacrylamide in the ceramic fiber dispersion is (0~40):1, and is not 0.
[0007] Preferably, the mass percentage concentration of nano-silica in the nano-silica dispersion is 0~42.5%, and not 0.
[0008] Preferably, the mass ratio of nano-silica in the nano-silica dispersion to ceramic fiber in the ceramic fiber dispersion is (0~0.5):1, and is not 0.
[0009] Preferably, the mass ratio of a portion of the mixture to the remainder of the mixture is 1:1.
[0010] Preferably, the freeze-drying temperature is -50 to -30°C, the pressure is 20 to 50 kPa, and the time is 24 to 48 hours.
[0011] Preferably, the sintering includes: heating to 200-300°C at a heating rate of 1-2°C / min, then heating to 800-1000°C at a heating rate of 1-2°C / min, and holding at that temperature for 2-4 hours.
[0012] The present invention also provides a rare earth zirconate high-entropy ceramic fiber aerogel prepared by the preparation method described above, comprising A2B2O7; The A 2-x B2+x In O7, A is a trivalent rare earth ion, B is a tetravalent zirconium ion, and A can be La, Nd, Sm, Gd, or Yb. The value of x ranges from 0 to 0.3. The rare earth zirconate high-entropy ceramic fiber aerogel has a porous structure.
[0013] Preferably, the molar ratio of La, Nd, Sm, Gd and Yb is 1:1:1:1:1; The molar ratio of A to B is 0.9:1.1.
[0014] The present invention also provides the application of the rare earth zirconate high-entropy ceramic fiber aerogel described in the above technical solution in high-temperature resistant thermal insulation ceramics.
[0015] This invention provides a method for preparing rare-earth zirconate high-entropy ceramic fiber aerogel, comprising the following steps: mixing a flexible rare-earth zirconate ceramic fiber membrane with deionized water containing polyacrylamide to obtain a ceramic fiber dispersion; the chemical composition of the flexible rare-earth zirconate ceramic fiber membrane is A. 2-x B 2+x O7; the A 2-x B 2+x In O7, A represents trivalent rare earth ions, B represents tetravalent zirconium ions, and A can be La, Nd, Sm, Gd, or Yb, with x ranging from 0 to 0.3. The nano-silica dispersion and the ceramic fiber dispersion are mixed to obtain a mixture. A portion of the mixture or a portion of the ceramic fiber dispersion is sequentially subjected to rotary freezing and ice crushing to obtain ice crystals. The ice crystals are added to the remaining mixture or the remaining ceramic fiber dispersion for liquid nitrogen freezing to obtain a frozen block. The frozen block is freeze-dried to obtain a fiber aerogel preform. The fiber aerogel preform is sintered to obtain the rare earth zirconate high-entropy ceramic fiber aerogel. The preparation method of this invention employs both ice-templating and freeze-drying methods. The ice-templating method adds ice crystals before liquid nitrogen freezing, preventing ice crystal growth from the bottom during freezing and ensuring fiber orientation, thus avoiding anisotropy in the preform. Freeze-drying removes the solvent through ice crystal sublimation, eliminating liquid phase surface tension throughout the process and preventing pore collapse and preform shrinkage. Therefore, the rare earth zirconate high-entropy ceramic fiber aerogel prepared by the preparation method of the present invention is composed of ceramic fibers overlapping each other, and has low density, high porosity, low thermal conductivity and certain compression resilience. Attached Figure Description
[0016] Figure 1 The room temperature thermal conductivity of the rare earth zirconate high-entropy ceramic fiber aerogels described in Examples 1-7; Figure 2 Comparison of the compression rebound state of the rare earth zirconate high-entropy ceramic fiber aerogels described in Examples 4 and 7; Figure 3 As described in Examples 1-7 (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2)1.8 Zr 2.2 SEM image of O7 high-entropy ceramic fiber aerogel. Detailed Implementation
[0017] This invention provides a method for preparing rare earth zirconate high-entropy ceramic fiber aerogel, comprising the following steps: A flexible rare-earth zirconate ceramic fiber membrane was mixed with deionized water containing polyacrylamide to obtain a ceramic fiber dispersion; the chemical composition of the flexible rare-earth zirconate ceramic fiber membrane is A. 2-x B 2+x O7; the A 2-x B 2+x In O7, A is a trivalent rare earth ion, B is a tetravalent zirconium ion, and A can be La, Nd, Sm, Gd, or Yb. The value of x ranges from 0 to 0.3. The nano-silica dispersion and the ceramic fiber dispersion are mixed to obtain a mixture; A portion of the mixture or a portion of the ceramic fiber dispersion is sequentially subjected to rotary freezing and ice crushing to obtain ice crystals; The ice crystals are added to the remaining mixture or the remaining ceramic fiber dispersion and frozen with liquid nitrogen to obtain frozen blocks; The frozen block was freeze-dried to obtain a fiber aerogel preform; The fiber aerogel preform is sintered to obtain the rare earth zirconate high-entropy ceramic fiber aerogel.
[0018] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.
[0019] This invention involves mixing a flexible rare-earth zirconate ceramic fiber membrane with deionized water containing polyacrylamide to obtain a ceramic fiber dispersion; the chemical composition of the flexible rare-earth zirconate ceramic fiber membrane is A. 2-x B 2+x O7; the A 2-x B 2+x In O7, A represents trivalent rare earth ions, B represents tetravalent zirconium ions, and A can be La, Nd, Sm, Gd, or Yb. The value of x ranges from 0 to 0.3.
[0020] In this invention, the flexible rare earth zirconate ceramic fiber membrane is preferably prepared by referring to the preparation method disclosed in the patent with publication number CN115286809A.
[0021] In this invention, before the mixing is performed, it is preferable to cut the flexible rare-earth zirconate ceramic fiber membrane into 1cm pieces. 2 Small pieces.
[0022] In this invention, the mass percentage concentration of polyacrylamide in the polyacrylamide-containing deionized water is preferably 0.1%.
[0023] In this invention, the mixing method is preferably shear dispersion, which preferably includes a first-stage shear dispersion, a second-stage shear dispersion, and a third-stage shear dispersion; the dispersion speed of the first-stage shear dispersion is preferably 7000~9000 rpm, more preferably 7000 rpm, 7500 rpm, 8000 rpm, 8500 rpm, or 9000 rpm; the time is preferably 10~15 min, more preferably 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min; the dispersion speed of the second-stage shear dispersion is preferably 12000~14000 rpm. The preferred speeds are 12000 rpm, 12500 rpm, 13000 rpm, 13500 rpm, or 14000 rpm; the preferred time is 10-15 min, more preferably 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min; the preferred dispersion rate of the third shear dispersion is 15000-17000 rpm, more preferably 15000 rpm, 16000 rpm, or 17000 rpm; the preferred time is 5-10 min, more preferably 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min. In this invention, the shear dispersion is preferably carried out in a high-speed shear disperser.
[0024] In this invention, the first stage of shear dispersion is used to macroscopically dissociate the flexible rare earth zirconate ceramic fiber membrane and protect the basic length of the fiber; the second stage of shear dispersion is used to open up the entangled fibers while avoiding damage to individual fibers; the third stage of shear dispersion is used to disassemble the remaining entangled fibers and make the individual fibers dispersed evenly.
[0025] In this invention, the mass ratio of flexible rare earth zirconate ceramic fiber membrane to polyacrylamide in the ceramic fiber dispersion is preferably (0~40):1, and not 0, more preferably 10:1, 20:1, 30:1 or 40:1.
[0026] In this invention, the chemical composition of the flexible rare-earth zirconate ceramic fiber membrane is A. 2-x B 2+x O7; the A 2- x B 2+xIn O7, A is a trivalent rare earth ion and B is a tetravalent zirconium ion. The A can be La, Nd, Sm, Gd and Yb. The molar ratio of A to B is preferably 0.9:1.1. The molar ratio of La, Nd, Sm, Gd and Yb is preferably 1:1:1:1:1.
[0027] After obtaining the ceramic fiber dispersion, the present invention mixes the nano silica dispersion and the ceramic fiber dispersion to obtain a mixture.
[0028] In this invention, the mass percentage concentration of nano-silica in the nano-silica dispersion is preferably 0-42.5%, and not 0, more preferably 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, or 42.5%. In an embodiment of this invention, the mass percentage concentration of nano-silica in the nano-silica dispersion can be 30%.
[0029] In this invention, the mass ratio of nano-silica in the nano-silica dispersion to ceramic fiber in the ceramic fiber dispersion is preferably (0~0.5):1, and not 0, more preferably 0.1:1, 0.2:1, 0.225:1, 0.3:1, 0.4:1 or 0.5:1.
[0030] In this invention, the main function of the polyacrylamide in the mixture is to help disperse the fibers. The silica will be present on some fiber surfaces and at fiber joints, which will play a role in bonding and overlapping the fibers. At the same time, controlling the mass ratio of nano silica and ceramic fibers within the above range can also avoid the problem of silica blocking the pores between fibers and thus failing to obtain a porous structure.
[0031] In this invention, the mixing is preferably carried out under magnetic stirring conditions. This invention does not impose any special limitations on the magnetic stirring process, and any process well known to those skilled in the art can be used.
[0032] After obtaining the mixture, the present invention sequentially subjectes a portion of the mixture or a portion of the ceramic fiber dispersion to rotary freezing and ice crushing to obtain ice crystals.
[0033] In this invention, the rotational freezing speed is preferably 1000~2000 rpm, more preferably 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm or 2000 rpm, the temperature is preferably -25~-35℃, more preferably -25℃, -30℃ or -35℃, and the time is preferably 5~8 min, more preferably 5 min, 6 min, 7 min or 8 min.
[0034] In this invention, the ice crushing condition is preferably that the ice crystal particle size does not exceed 800µm, and more preferably that the ice crystal particle size does not exceed 500µm.
[0035] In this invention, the mass ratio of a portion of the mixture to the remainder of the mixture is preferably 1:1; or the mass ratio of a portion of the ceramic fiber dispersion to the remainder of the ceramic fiber dispersion is preferably 1:1.
[0036] After obtaining the ice crystals, the present invention adds the ice crystals to the remaining mixture or the remaining ceramic fiber dispersion for liquid nitrogen freezing to obtain frozen blocks.
[0037] In this invention, the process of adding the ice crystals to the remaining mixture or the remaining ceramic fiber dispersion is preferably carried out under stirring conditions. The stirring speed is preferably 100~500 rpm, more preferably 100 rpm, 200 rpm, 300 rpm, 00 rpm or 500 rpm; the stirring time is preferably 30 s.
[0038] In this invention, the process of adding the ice crystals to the remaining mixture or the remaining ceramic fiber dispersion allows the ice crystals to directly skip the liquid sublimation into water vapor under low temperature and low pressure, retaining the complete pore structure. In this process, there is no liquid surface tension, ensuring that the three-dimensional network formed by the fiber overlap will not undergo significant deformation and shrinkage during the drying process.
[0039] In this invention, the liquid nitrogen freezing process is preferably carried out by injecting the mixture obtained after adding the ice crystals to the remaining mixture into the mold, placing a copper plate above the liquid nitrogen, and then placing the mold on the copper plate for freezing.
[0040] After obtaining the frozen block, the present invention freeze-dries the frozen block to obtain a fiber aerogel preform.
[0041] In this invention, the freeze-drying temperature is preferably -50~-30℃, more preferably -50℃, -40℃ or -30℃; the pressure is preferably 20~50kPa, more preferably 20kPa, 30kPa, 40kPa or 50kPa; and the time is preferably 24~48h, more preferably 24h, 36h or 8h.
[0042] After obtaining the fiber aerogel preform, the present invention sinters the fiber aerogel preform to obtain the rare earth zirconate high-entropy ceramic fiber aerogel.
[0043] In this invention, the sintering preferably includes: heating to 200-300°C at a heating rate of 1-2°C / min, then heating to 800-1000°C at a heating rate of 1-2°C / min and holding at that temperature for 2-4 hours; more preferably, heating to 300°C at a heating rate of 1°C / min, then heating to 800°C at a heating rate of 2°C / min and holding at that temperature for 2 hours.
[0044] In this invention, since increased temperature leads to grain growth, which increases fiber brittleness and affects performance, controlling the sintering temperature and time within the above-mentioned range can avoid the occurrence of the above problems. Specifically, polyacrylamide will remove moisture and organic solvents at 30~200℃, the molecular chain will break at 20~300℃, and the amide group and other side chains will decompose to form nitrogen-containing compounds and carbon dioxide at 300~800℃, while the main chain will decompose into carbon dioxide. Since a large amount of gas will be generated during the decomposition process, a slower heating rate was selected.
[0045] This invention also provides a rare-earth zirconate high-entropy ceramic fiber aerogel prepared by the preparation method described above, comprising A 2-x B 2+x O7; The A 2-x B 2+x In O7, A is a trivalent rare earth ion, B is a tetravalent zirconium ion, and A can be La, Nd, Sm, Gd, or Yb. The value of x ranges from 0 to 0.3. The rare earth zirconate high-entropy ceramic fiber aerogel has a porous structure.
[0046] In this invention, the molar ratio of La, Nd, Sm, Gd and Yb is preferably 1:1:1:1:1; The molar ratio of A to B is 0.9:1.1.
[0047] In this invention, the density of the rare earth zirconate high-entropy ceramic fiber aerogel is preferably 1.24~1.64 mg / cm³. 3 The thermal conductivity is preferably 0.0279~0.0313 W / (m·K), and the porosity is preferably 99.96%~99.98%.
[0048] In this invention, the rare earth zirconate high-entropy ceramic fiber aerogel preferably also includes silicon dioxide; the mass percentage of silicon dioxide in the rare earth zirconate high-entropy ceramic fiber aerogel is preferably ≤22.5%.
[0049] In this invention, the rare earth zirconate high-entropy ceramic fiber aerogel is formed by overlapping rare earth zirconate high-entropy ceramic (A2B2O7) fibers, with silicon dioxide acting as a bridging agent.
[0050] This invention also provides the application of the rare earth zirconate high-entropy ceramic fiber aerogel described above in high-temperature insulating ceramics. This invention does not impose any special limitations on the method of application; any method well-known to those skilled in the art can be used.
[0051] The following detailed description, in conjunction with embodiments, illustrates the rare-earth zirconate high-entropy ceramic fiber aerogel, its preparation method, and its applications. However, these descriptions should not be construed as limiting the scope of protection of this invention.
[0052] Example 1 1.15 g lanthanum chloride hexahydrate, 1.17 g neodymium chloride hexahydrate, 1.19 g samarium chloride hexahydrate, 1.22 g gadolinium chloride hexahydrate, 1.27 g ytterbium chloride hexahydrate, and 6.44 g zirconium oxychloride octahydrate were dissolved in 35.2 g anhydrous methanol. After complete dissolution, 4.16 g acetylacetone and 9.8 g triethylamine were added sequentially (the molar ratio of zirconium oxychloride octahydrate:acetylacetone:triethylamine was 1:2.1:4.9). After stirring for 5 h, a clear, bright yellow solution was obtained. The transparent bright yellow solution was dried under reduced pressure at 40°C to obtain a zirconium-rare earth acetylacetone polymer containing triethylamine hydrochloride. The zirconium-rare earth acetylacetone polymer containing triethylamine hydrochloride was soaked in 80 mL of acetone for 72 h. Then the triethylamine hydrochloride precipitate was filtered off to obtain an acetone solution containing the zirconium-rare earth acetylacetone polymer. The solution was clear and transparent and pale yellow. The acetone solution containing the zirconium-rare earth acetylacetone polymer was dried under reduced pressure at 40°C to obtain the zirconium-rare earth acetylacetone polymer.
[0053] 2g of the zirconium-rare earth acetylacetone polymer was dissolved in 4g of anhydrous methanol, and 0.08g of polyvinylpyrrolidone (PVP) was added. The mixture was magnetically stirred for 2h until the PVP was completely dissolved to obtain a transparent and clear spinning solution. The spinning solution was electrospun to obtain a zirconium-rare earth acetylacetone polymer precursor fiber membrane. The electrospinning voltage was 18 kV, the electrospinning humidity was 30%, the feed speed was 0.0015 mm / s, and the distance from the needle to the receiving shaft was 15 cm. After drying in an oven at 80°C for 2 hours, it was calcined in air atmosphere. The heating rate was 1°C / min before 300°C and 5°C / min after 300°C. The calcination temperature was 800°C and the holding time was 2 hours to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane; Add 0.05g of polyacrylamide to 50mL of deionized water to obtain deionized water containing polyacrylamide; 0.2g of the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane cut into 1cm pieces 2 The small pieces were dispersed in the polyacrylamide-containing deionized water using a high-shear disperser (shear dispersion conditions: 7000 r / min). 10min + 12000r / min 10min + 17000r / min 5min), obtained (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 fiber suspension; 25g of the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The O7 fiber suspension was poured onto a rotary freezing drum (2000 rpm, -35°C, 5 min), and the resulting ice layer was broken up and collected by a scraper to obtain ice crystals (particle size 200~500 μm). The ice crystals and the remaining (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 After mixing the O7 fiber suspension, stir rapidly for 30 seconds (300 rpm) to obtain a mixed suspension of ice crystals and fibers. The mixed suspension was injected into a mold, a copper plate was placed above the liquid nitrogen, and the mold was then placed on the copper plate for freezing for 3 hours to obtain a frozen block. The frozen block was dried in a vacuum freeze dryer at 20 kPa and -50°C for 24 h to obtain a rare earth zirconate high-entropy ceramic fiber aerogel preform. The rare-earth zirconate high-entropy ceramic fiber aerogel preform was calcined in air atmosphere. The heating rate was 1℃ / min before 300℃ and 2℃ / min after 300℃. The calcination temperature was 800℃ and the holding time was 2h to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber aerogel.
[0054] The (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The average density of O7 high-entropy ceramic fiber aerogel is 1.24 mg / cm³. 3 The porosity is 99.98%, and the room temperature thermal conductivity is 0.0289 W / (m·K) (e.g. Figure 1 As shown in the figure, it can recover after withstanding approximately 15% deformation.
[0055] Example 2 (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The preparation method of O7 high-entropy ceramic fiber membrane is described in Example 1; Add 0.05g of polyacrylamide to 50mL of deionized water to obtain deionized water containing polyacrylamide; 0.2g of the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane cut into 1cm pieces 2 The small pieces were dispersed in the polyacrylamide-containing deionized water using a high-shear disperser (shear dispersion conditions: 7000 r / min). 10min + 12000r / min 10min + 17000r / min 5min), obtained (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb0.2 ) 1.8 Zr 2.2 O7 fiber suspension; In the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 Add 0.05g of nano-silica suspension (30wt%) to the O7 fiber suspension, and stir magnetically at 300r / min for 2h to mix it evenly to obtain a mixture. 25g of the mixture was poured onto a rotary freezing drum (2000rpm, -35℃, 5min), and the resulting ice layer was broken up and collected by a scraper to obtain ice crystals (particle size 200~500μm). The ice crystals are mixed with the remaining mixture and then stirred rapidly for 30 seconds (300 rpm) to obtain a mixed suspension of ice crystals and fibers. The mixed suspension was injected into a mold, a copper plate was placed above the liquid nitrogen, and the mold was then placed on the copper plate for freezing for 3 hours to obtain a frozen block. The frozen block was dried in a vacuum freeze dryer at 20 kPa and -50°C for 24 h to obtain a rare earth zirconate high-entropy ceramic fiber aerogel preform. The rare-earth zirconate high-entropy ceramic fiber aerogel preform was calcined in air atmosphere. The heating rate was 1℃ / min before 300℃ and 2℃ / min after 300℃. The calcination temperature was 8000℃ and the holding time was 2h to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber aerogel; The (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The average density of O7 high-entropy ceramic fiber aerogel is 1.32 mg / cm³. 3 The porosity is 99.98%, and the room temperature thermal conductivity is 0.0287 W / (m·K) (e.g. Figure 1 As shown in the figure, it can recover after withstanding approximately 15% deformation.
[0056] Example 3 (La0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The preparation method of O7 high-entropy ceramic fiber membrane is described in Example 1; Add 0.05g of polyacrylamide to 50mL of deionized water to obtain deionized water containing polyacrylamide; 0.2g of the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane cut into 1cm pieces 2 The small pieces were dispersed in the polyacrylamide-containing deionized water using a high-shear disperser (shear dispersion conditions: 7000 r / min). 10min + 12000r / min 10min + 17000r / min (5min) to obtain (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 fiber suspension; In the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 Add 0.1g of nano-silica suspension (30wt%) to the O7 fiber suspension, and stir magnetically at 300r / min for 2h to mix it evenly to obtain a mixture; 25g of the mixture was poured onto a rotary freezing drum (2000rpm, -35℃, 5min), and the resulting ice layer was broken up and collected by a scraper to obtain ice crystals (particle size 200~500μm). The ice crystals are mixed with the remaining mixture and then stirred rapidly for 30 seconds (300 rpm) to obtain a mixed suspension of ice crystals and fibers. The mixed suspension was injected into a mold, a copper plate was placed above the liquid nitrogen, and the mold was then placed on the copper plate for freezing for 3 hours to obtain a frozen block. The frozen block was dried in a vacuum freeze dryer at 20 kPa and -50°C for 24 h to obtain a rare earth zirconate high-entropy ceramic fiber aerogel preform. The rare-earth zirconate high-entropy ceramic fiber aerogel preform was calcined in air atmosphere. The heating rate was 1℃ / min before 300℃ and 2℃ / min after 300℃. The calcination temperature was 8000℃ and the holding time was 2h to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber aerogel; The (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The average density of O7 high-entropy ceramic fiber aerogel is 1.36 mg / cm³. 3 The porosity is 99.97%, and the room temperature thermal conductivity is 0.0284 W / (m·K) (e.g. Figure 1 As shown in the figure, it can recover after withstanding approximately 18% deformation.
[0057] Example 4 (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The preparation method of O7 high-entropy ceramic fiber membrane is described in Example 1; Add 0.05g of polyacrylamide to 50mL of deionized water to obtain deionized water containing polyacrylamide; 0.2g (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane cut into 1cm pieces 2 The small pieces were dispersed in the polyacrylamide-containing deionized water using a high-shear disperser (shear dispersion conditions: 7000 r / min). 10min + 12000r / min 10min + 17000r / min 5min), obtained (La 0.2Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 fiber suspension; In the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 Add 0.15g of nano-silica suspension (30wt%) to the O7 fiber suspension, and stir magnetically at 300r / min for 2h to mix it evenly to obtain a mixture. 25g of the mixture was poured onto a rotary freezing drum (2000rpm, -35℃, 5min), and the resulting ice layer was broken up and collected by a scraper to obtain ice crystals (particle size 200~500μm). The ice crystals are mixed with the remaining mixture and then rapidly stirred for 30 seconds (300 rpm) to obtain a mixed suspension of ice crystals and fibers. The mixed suspension was injected into a mold, a copper plate was placed above the liquid nitrogen, and the mold was then placed on the copper plate for freezing for 3 hours to obtain a frozen block. The frozen block was dried in a vacuum freeze dryer at 20 kPa and -50°C for 24 h to obtain a rare earth zirconate high-entropy ceramic fiber aerogel preform. The rare-earth zirconate high-entropy ceramic fiber aerogel preform was calcined in air atmosphere. The heating rate was 1℃ / min before 300℃ and 2℃ / min after 300℃. The calcination temperature was 8000℃ and the holding time was 2h to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber aerogel; The (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The average density of O7 high-entropy ceramic fiber aerogel is 1.46 mg / cm³. 3 The porosity is 99.97%, and the room temperature thermal conductivity is 0.0279 W / (m·K) (e.g. Figure 1 As shown in the figure, it can recover after withstanding approximately 20% deformation.
[0058] Example 5 (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The preparation method of O7 high-entropy ceramic fiber membrane is described in Example 1; Add 0.05g of polyacrylamide to 50mL of deionized water to obtain deionized water containing polyacrylamide; 0.2g of the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane cut into 1cm pieces 2 The small pieces were dispersed in the polyacrylamide-containing deionized water using a high-shear disperser (shear dispersion conditions: 7000 r / min). 10min + 12000r / min 10min + 17000r / min 5min), obtained (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 fiber suspension; In the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 Add 0.2g of nano-silica suspension (30wt%) to the O7 fiber suspension, and stir magnetically at 300r / min for 2h to mix it evenly to obtain a mixture; 25g of the mixture was poured onto a rotary freezing drum (2000rpm, -35℃, 5min), and the resulting ice layer was broken up and collected by a scraper to obtain ice crystals (particle size 200~500μm). The ice crystals are mixed with the remaining mixture and then stirred rapidly for 30 seconds (300 rpm) to obtain a mixed suspension of ice crystals and fibers. The mixed suspension was injected into a mold, a copper plate was placed above the liquid nitrogen, and the mold was then placed on the copper plate for freezing for 3 hours to obtain a frozen block. The frozen block was dried in a vacuum freeze dryer at 20 kPa and -50°C for 24 h to obtain a rare earth zirconate high-entropy ceramic fiber aerogel preform. The rare-earth zirconate high-entropy ceramic fiber aerogel preform was calcined in air atmosphere. The heating rate was 1℃ / min before 300℃ and 2℃ / min after 300℃. The calcination temperature was 800℃ and the holding time was 2h to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber aerogel; The (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The average density of O7 high-entropy ceramic fiber aerogel is 1.49 mg / cm³. 3 The porosity is 99.97%, and the room temperature thermal conductivity is 0.0285 W / (m·K) (e.g. Figure 1 As shown, it can only withstand 10% of the deformation before recovering.
[0059] Example 6 (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The preparation method of O7 high-entropy ceramic fiber membrane is described in Example 1; Add 0.05g of polyacrylamide to 50mL of deionized water to obtain deionized water containing polyacrylamide; 0.2g of the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane cut into 1cm pieces 2 The small pieces were dispersed in the polyacrylamide-containing deionized water using a high-shear disperser (shear dispersion conditions: 7000 r / min). 10min + 12000r / min 10min + 17000r / min 5min), obtained (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 fiber suspension; In the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 Add 0.25g of nano-silica suspension (30wt%) to the O7 fiber suspension, and stir magnetically at 300r / min for 2h to mix it evenly to obtain a mixture. 25g of the mixture was poured onto a rotary freezing drum (2000rpm, -35℃, 5min), and the resulting ice layer was broken up and collected by a scraper to obtain ice crystals (particle size 200~500μm). The ice crystals are mixed with the remaining mixture and then stirred rapidly for 30 seconds (300 rpm) to obtain a mixed suspension of ice crystals and fibers. The mixed suspension was injected into a mold, a copper plate was placed above the liquid nitrogen, and the mold was then placed on the copper plate for freezing for 3 hours to obtain a frozen block. The frozen block was dried in a vacuum freeze dryer at 20 kPa and -50°C for 24 h to obtain a rare earth zirconate high-entropy ceramic fiber aerogel preform. The rare-earth zirconate high-entropy ceramic fiber aerogel preform was calcined in air atmosphere. The heating rate was 1℃ / min before 300℃ and 2℃ / min after 300℃. The calcination temperature was 8000℃ and the holding time was 2h to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber aerogel; The (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2The average density of O7 high-entropy ceramic fiber aerogel is 1.51 mg / cm³. 3 The porosity is 99.96%, and the room temperature thermal conductivity is 0.0305 W / (m·K) (e.g. Figure 1 As shown, it can only withstand 5% deformation before recovering.
[0060] Example 7 (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The preparation method of O7 high-entropy ceramic fiber membrane is described in Example 1; Add 0.05g of polyacrylamide to 50mL of deionized water to obtain deionized water containing polyacrylamide; 0.2g of the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber membrane cut into 1cm pieces 2 The small pieces were dispersed in the polyacrylamide-containing deionized water using a high-shear disperser (shear dispersion conditions: 7000 r / min). 10min + 12000r / min 10min + 17000r / min 5min), obtained (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 fiber suspension; In the (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 Add 0.3g of nano-silica suspension (30wt%) to the O7 fiber suspension, and stir magnetically at 300r / min for 2h to mix it evenly to obtain a mixture; 25g of the mixture was poured onto a rotary freezing drum (2000rpm, -35℃, 5min), and the resulting ice layer was broken up and collected by a scraper to obtain ice crystals (particle size 200~500μm). The ice crystals are mixed with the remaining mixture and then stirred rapidly for 30 seconds (300 rpm) to obtain a mixed suspension of ice crystals and fibers. The mixed suspension was injected into a mold, a copper plate was placed above the liquid nitrogen, and the mold was then placed on the copper plate for freezing for 3 hours to obtain a frozen block. The frozen block was dried in a vacuum freeze dryer at 20 kPa and -50°C for 24 h to obtain a rare earth zirconate high-entropy ceramic fiber aerogel preform. The rare-earth zirconate high-entropy ceramic fiber aerogel preform was calcined in air atmosphere. The heating rate was 1℃ / min before 300℃ and 2℃ / min after 300℃. The calcination temperature was 8000℃ and the holding time was 2h to obtain (La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 O7 high-entropy ceramic fiber aerogel; The (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr 2.2 The average density of O7 high-entropy ceramic fiber aerogel is 1.64 mg / cm³. 3 The porosity is 99.96%, and the room temperature thermal conductivity is 0.0313 W / (m·K) (e.g. Figure 1 As shown, it can only withstand about 2% of deformation before recovering.
[0061] Figure 2 This image compares the compression and rebound states of the rare-earth zirconate high-entropy ceramic fiber aerogels described in Examples 4 and 7. (a) is an image of the rare-earth zirconate high-entropy ceramic fiber aerogel described in Example 4 under compression; (b) is an image of the rare-earth zirconate high-entropy ceramic fiber aerogel described in Example 7 under compression; (c) is an image of the rare-earth zirconate high-entropy ceramic fiber aerogel described in Example 4 after release; and (d) is an image of the rare-earth zirconate high-entropy ceramic fiber aerogel described in Example 7 after release. Figure 2 It is known that adding too much silica will reduce its compression resilience. Figure 3 As described in Examples 1-7 (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Yb 0.2 ) 1.8 Zr2.2 SEM images of O7 high-entropy ceramic fiber aerogel, where (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Example 5, (f) is Example 6, and (g) is Example 7; Figure 3 It is known that when the amount of Si added exceeds 22.5% (Example 3), the excess nano silica sol will not only cover the fiber surface, but also fill the gaps between the fibers to form a layered structure, thereby reducing its thermal conductivity and compression resilience.
[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing rare earth zirconate high-entropy ceramic fiber aerogel, characterized in that, Includes the following steps: A flexible rare-earth zirconate ceramic fiber membrane was mixed with deionized water containing polyacrylamide to obtain a ceramic fiber dispersion; the chemical composition of the flexible rare-earth zirconate ceramic fiber membrane is A. 2-x B 2+x O7; the A 2-x B 2+x In O7, A is a trivalent rare earth ion, B is a tetravalent zirconium ion, and A can be La, Nd, Sm, Gd, or Yb. The value of x ranges from 0 to 0.
3. The nano-silica dispersion and the ceramic fiber dispersion are mixed to obtain a mixture; A portion of the mixture or a portion of the ceramic fiber dispersion is sequentially subjected to rotary freezing and ice crushing to obtain ice crystals; The ice crystals are added to the remaining mixture or the remaining ceramic fiber dispersion and frozen with liquid nitrogen to obtain frozen blocks; The frozen block was freeze-dried to obtain a fiber aerogel preform; The fiber aerogel preform is sintered to obtain the rare earth zirconate high-entropy ceramic fiber aerogel.
2. The preparation method according to claim 1, characterized in that, The polyacrylamide concentration in the deionized water containing polyacrylamide is 0.1% by mass. The mass ratio of flexible rare earth zirconate ceramic fiber membrane to polyacrylamide in the ceramic fiber dispersion is (0~40):1, and is not 0.
3. The preparation method according to claim 1, characterized in that, The mass percentage concentration of nano-silica in the nano-silica dispersion is 0~42.5%, and is not 0.
4. The preparation method according to claim 1, characterized in that, The mass ratio of nano-silica in the nano-silica dispersion to ceramic fiber in the ceramic fiber dispersion is (0~0.5):1, and is not 0.
5. The preparation method according to claim 1, characterized in that, The mass ratio of a portion of the mixture to the remainder of the mixture is 1:
1.
6. The preparation method according to claim 1, characterized in that, The freeze-drying temperature is -50~-30℃, the pressure is 20~50kPa, and the time is 24~48h.
7. The preparation method according to claim 1, characterized in that, The sintering process includes: heating to 200-300°C at a heating rate of 1-2°C / min, then heating to 800-1000°C at a heating rate of 1-2°C / min and holding at that temperature for 2-4 hours.
8. The rare-earth zirconate high-entropy ceramic fiber aerogel prepared by the preparation method according to any one of claims 1 to 7, characterized in that, Including A 2-x B 2+x O7; The A 2-x B 2+x In O7, A is a trivalent rare earth ion, B is a tetravalent zirconium ion, and A can be La, Nd, Sm, Gd, or Yb. The value of x ranges from 0 to 0.
3. The rare earth zirconate high-entropy ceramic fiber aerogel has a porous structure.
9. The rare earth zirconate high-entropy ceramic fiber aerogel as described in claim 8, characterized in that, The molar ratio of La, Nd, Sm, Gd and Yb is 1:1:1:1:1; The molar ratio of A to B is 0.9:1.
1.
10. The application of the rare earth zirconate high-entropy ceramic fiber aerogel according to claim 8 or 9 in high-temperature resistant thermal insulation ceramics.
Citation Information
Patent Citations
Flexible rare earth zirconate high-entropy ceramic fiber membrane as well as preparation and application thereof
CN115286809A